1995
DOI: 10.1159/000213675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Colorectal Cancer’s 5-Year Survival

Abstract: The aim of this study was to ascertainthe 5-year survival figures of 171 consecutive colorectal cancer patients in southwestern Finland, the differences between various age groups, and which clinical variables predict poor outcome. The mean age at the time of diagnosis was 67 years in men and 69 years in women. The 5-year survival was lower in older patients, especially in those over 80 years with concomitant diseases. However, the colorectal cancer mortality did not differ between the three age groups: < 65, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The prognosis depends to a great extent on the metastizing tendency of the tumor and this is often lower in older patients (Kemppainen et al 1995). In an extensive autopsy study it was found that liver metastases from malignant tumors located in the area of the portal circulation occurred with an equal frequency in the younger and older age groups (Pejchl 1990).…”
Section: Cancers Through Aging and Senescence Of The Human Organism: mentioning
confidence: 99%
“…The prognosis depends to a great extent on the metastizing tendency of the tumor and this is often lower in older patients (Kemppainen et al 1995). In an extensive autopsy study it was found that liver metastases from malignant tumors located in the area of the portal circulation occurred with an equal frequency in the younger and older age groups (Pejchl 1990).…”
Section: Cancers Through Aging and Senescence Of The Human Organism: mentioning
confidence: 99%